PHYTOREMEDIATION OF SALT- AFFECTED SOILS AT AL- JAZEERA NORTHERN IRRIGRATION PROJECT/ NINAVAH/ IRAQ - Amer W. Abdul-Kareem; Khalid Ekhlayef Nazzal (Mesopotamia Journal of Agriculture)
Soil salinity is one of the most serious limiting factors that affect plant growth and productivity of various crops in arid regions. Methods commonly used to combat salinity are either classical or new using halophytes.This study was conducted at plastichouse in order to evaluate the efficiency of Atriplexhalimus in salt removal from saline, saline-sodic soils of Al-jazeera project in Ninavah province. Plantation with A.halimus decreased electrical conductivity for saline- sodic soil from 39.2 to 26.5dS.m-1 and from 6.2 to 4.9 dS.m-1 for saline soil. Sodium adsorption ratio declined to half and 28.6% for saline- sodic and saline soils respectively. The current study revealed an increased efficiency of Atriplexhalimus with increasing salinity which suggest it a good candidate for soil desalination in arid and semiarid regions.